2020
DOI: 10.3390/info11060297
|View full text |Cite
|
Sign up to set email alerts
|

How Does Technological and Financial Literacy Influence SME Performance: Mediating Role of ERM Practices

Abstract: The knowledge-based view (KBV) in the development of small and medium-sized enterprises (SMEs) is a debatable topic in the current literature. Although convergence of technological and financial literacy (techno-finance literacy) is an essential knowledge-based tool to address rapid digitalization of business, the influence of techno-finance literacy in the development of SMEs is still not adequately researched. Drawing upon KBV, we developed a single-mediator structural model with an aim to explore the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 86 publications
9
64
0
7
Order By: Relevance
“…The outcome shows the regression model, with four independent variables, where budgeting and access to finance have the largest absolute value at 0.425 and 0.373 respectively, which indicates a unique account for the largest proportion of the variance in the regression model. The significant effect of financial awareness on financial sustainability is in line with the findings of a study by Usama and Yusoff (2018), which observed that financial awareness had a clear and great effect on the financial sustainability of Nigerian SMEs, and a study by Kulathunga et al (2020) which also noticed that financial awareness had a significant influence on the performance of SMEs. The results of this study are therefore consistent with those of Usama and Yusoff (2019) who have defined financial awareness as an essential component of the intellectual capital of organisations and have concluded that intellectual capital has had a major impact on the financial sustainability of SMEs.…”
Section: Figure 3: Age Groupsupporting
confidence: 87%
“…The outcome shows the regression model, with four independent variables, where budgeting and access to finance have the largest absolute value at 0.425 and 0.373 respectively, which indicates a unique account for the largest proportion of the variance in the regression model. The significant effect of financial awareness on financial sustainability is in line with the findings of a study by Usama and Yusoff (2018), which observed that financial awareness had a clear and great effect on the financial sustainability of Nigerian SMEs, and a study by Kulathunga et al (2020) which also noticed that financial awareness had a significant influence on the performance of SMEs. The results of this study are therefore consistent with those of Usama and Yusoff (2019) who have defined financial awareness as an essential component of the intellectual capital of organisations and have concluded that intellectual capital has had a major impact on the financial sustainability of SMEs.…”
Section: Figure 3: Age Groupsupporting
confidence: 87%
“…[96] also evidenced the mediating role of SM in the context of online service failures and recovery strategy in SMEs. In addition, [98] strengthen the mediating role of SM motives between trait emotional intelligence and problematic SM use among students at a Turkish State Uni-versity. Similarly, Olanrewaju et al (2020) [34] suggested the mediating role of SM adoption between TOE constructs and SME performance, while [99] recommended a segmentation approach to develop a hypothesis for mediation testing.…”
Section: Mediating Role Of Social Media Adoptionmentioning
confidence: 61%
“…Primary respondents targeted were owners, managers, and CEOs, as they were judged to be the most knowledgeable about their company environments and performance [96,97]. Following the proposed global industry classification standard, the targeted SMEs operated as follows: consumer discretionary, consumer staples, information technology, financials, and communication services [98].…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…The mediation role of financial literation in ensuring MSMEs sustainability: An organizational characteristics perspective by Arik Prasetya, Kusdi Rahardjo, Mukhammad Kholid Mawardi, Raden Rustam Hidayat, Yudha Prakasa of internal firm capability that can complement access to finance to achieve superior growth outcomes." Organizations that are rapidly using new technologies to create collaborative work and knowledge-sharing culture can uplift their organizational performance in an efficient way (Kulathunga et al, 2020). Besides, Brown et al (2017) added that cultural differences prove to be significant financial literacy predictors between students with different languages and socio-economic backgrounds.…”
Section: Sustainability In the Msmes Sectormentioning
confidence: 99%